Conservative Linear Difference Scheme for Rosenau-KdV Equation - Jinsong Hu; Youcai Xu; Bing Hu (Advances in Mathematical Physics)
A conservative three-level linear finite difference scheme for the numerical solution of the initial-boundary value problem of Rosenau-KdV equation is proposed. The difference scheme simulates two conservative quantities of the problem well. The existence and uniqueness of the difference solution are proved. It is shown that the finite difference scheme is of second-order convergence and unconditionally stable. Numerical experiments verify the theoretical results.